Comparison of lung tissue concentrations of nebulized ceftazidime in ventilated piglets: ultrasonic versus vibrating plate nebulizers - Ferrari, Fabio [UNESP]; Liu, Zhi-Hai; Lu, Qin; Becquemin, Marie-Helene; Louchahi, Kamel; Aymard, Guy; Marquette, Charles-Hugo; Rouby, Jean-Jacques (Springer, 2008)
Objective: To compare the efficiency of an Aeroneb Pro vibrating plate and an Atomisor MegaHertz ultrasonic nebulizer for providing ceftazidime distal lung deposition.Design: In vitro experiments. One gram of cetazidime was nebulized in respiratory circuits and mass median aerodynamic diameter of particles generated by ultrasonic and vibrating plate nebulizers was compared using a laser velocimeter. In vivo experiments. Lung tissue concentrations and extrapulmonary depositions were measured in ten anesthetized ventilated piglets with healthy lungs that received 1 g of ceftazidime by nebulization with either an ultrasonic (n = 5), or a vibrating plate (n = 5) nebulizer.Setting: A two-bed Experimental Intensive Care Unit of a University School of Medicine.Intervention: Following sacrifice, 5 subpleural specimens were sampled in dependent and nondependent lung regions for measuring ceftazidime lung tissue concentrations by high-performance liquid chromatography.Measurements and results: Mass median aerodynamic diameters generated by both nebulizers were similar with more than 95% of the particles between 0.5 and 5 mu m. Lung tissue concentrations were 553 +/- 123 [95% confidence interval: 514-638] mu g g(-1) using ultrasonic nebulizer, and 452 +/- 172 [95% confidence interval: 376-528] mu g g(-1) using vibrating plate nebulizers (NS). Extrapulmonary depositions were, respectively, of 38 +/- 5% (ultrasonic) and 34 +/- 4% (vibrating plate) (NS).Conclusions: Vibrating plate nebulizer is comparable to ultrasonic nebulizers for ceftazidime nebulization. It may represent a new attractive technology for inhaled antibiotic therapy.
Keywords: ultrasonic; vibrating plate; nebulizer; nebulization of antibiotics; lung tissue concentration